perkembangan peradaban islam di KERAJAAN TURKI USMANI - Rahmawati, Rahmawati (RIHLAH, 2013)
Ottoman empire as the kingdom that survived until the 20th century more attention on the issue of military and territorial expansion. Education and intellectual movement is directed to strengthen the stability of the royal empire. There is a very close relationship between the military interest, religion, power, and reforms in education. Onthe one hand, the militaryis injectedsohardonthe whole societyandthe empirebystrengtheningthe powerof the Ottoman Empireandonthe other hand, the socio-religious authoritiesis bound toIslamic lawandalso developsunderstandingSufioriented.onthe otherhand, energy-Muslim scholarsof the timerun outjustforsheerproducesideas inmilitaryfield. For them, the demands ofthe timeswhich requiresMuslimsto masterscienceandtechnologyis the reasonthatlearningisanobligation, without having tobe embarrassedorlooked away, althoughscienceandtechnologyfrom the West